Criticizing the Political System and the Normativity Foundations Through Joseph Raz's Legal and Philosophical Thought - Silalahi, Artha Debora (Faculty of Law, Universitas Gadjah Mada, 2025)
Abstract This article explores constitutional legitimacy through the legal and philosophical lens of Joseph Raz, focusing on the dynamic relationship between political systems, normative reasoning, and public justification. Raz contends that legal authority cannot rely solely on institutional power or formal procedures; it must be supported by reasons that individuals can endorse as morally and rationally acceptable. This insight is especially relevant to constitutional interpretation, where judges must navigate between textual fidelity, evolving democratic norms, and political pressures. Divided into four key discussions, the article first tracesthe foundations of Raz’s legal philosophy and its political context. Then, it examines the political system, public reason, and judicial interpretation in Raz’s framework. The third section focuses on the normativity foundations in Raz’s legal and political philosophy landscape. Finally, the article applies these insights to the Indonesian context, where constitutional judging faces challenges from politicized reason justification. Using a philosophical-legal method, this article argues that a Razian approach can help preserve public trust and legal legitimacy by grounding judges to act not only with legal precision but also with ethical discernment, civic responsibility, and publicly justifiable norms rather than in institutional dominance. Abstrak Artikel ini menyajikan analisis tentang legitimasi konstitusi melalui pendekatan hukum dan filsafat Joseph Raz, dengan menyoroti hubungan antara sistem politik, alasan normatif, dan pembenaran publik. Raz berpendapat bahwa otoritas hukum tidak dapat semata-mata didasarkan pada kekuasaan institusional atau prosedur formal, melainkan harus dibangun atas dasar alasan yang dapat diterima secara moral dan rasional oleh masyarakat. Pandangan ini sangat relevan dalam praktik interpretasi konstitusi, khususnya di negara seperti Indonesia, di mana tekanan politik kerap memengaruhi proses pengambilan keputusan yudisial. Artikelini terbagi dalam empat bagian utama. Bagian pertama membahas dasar-dasar filsafat hukum Raz dan konteks politiknya. Bagian kedua mengkaji konsep sistem politik, nalar publik, and interpretasi yudisial dalam kerangka pemikiran filosofis Raz. Bagian ketiga mengulas fondasi normativitas dalam acuan pemikiran filsafathukum dan politik Raz. Bagian keempat menerapkan pemikiran Raz untuk menelaah situasi Indonesia, di mana penegakan konstitusi menghadapi ragam tantangan yaitu justifikasi alasan yang dipolitisasi. Dengan menggunakan metode penelitian filsafat dalam kerangka philosophical-legal, artikel ini menunjukkanbahwa pendekatan Raz dapat membantu menjaga kepercayaan publik dan legitimasi hukum dengan membumikan hakim harus bertindak tidak hanya berdasarkan presisi hukum tetapi dengan kearifan etis, tanggung jawab sipil, dan norma-norma yang dapat dibenarkan secara publik daripada dalam dominasi kelembagaan.